Ecos do Romantismo em A casa das sete mulheres - Leonhardt, Daniela (2014)
The object of this research is the novel The House of Seven Women (2002), by Leticia Wierzchowski, which tells the story of the women of General Bento Gonçalves`s family. They are isolated on the General`s farm (Fazenda da Barra) so that they are kept safe during the Farroupilha Revolution, which lasted ten years. This novel was internationally recognized, as it was published in six other countries, including Germany, Greece and Spain. It was released in the beginning of the twenty-first century, but it seems that the influences of Romanticism resisted the changes that have occurred in literature since the nineteenth century. Besides that, aspects of works produced during the romantic period are restored and maintained. This research aims at examining how this late Romanticism contributes for the building of a collective imaginary, as well as at investigating the reason for the popularity of a novel that has less affinity with contemporary works than with the ones produced in the nineteenth century. It also verifies if the novel can be considered a contemporary work or if the presence of elements which reproduce aspects of Romanticism does not allow this classification. For this, some key contributions of studies regarding contemporaneity are listed, so that it is possible to verify in which aspects the novel gets close or distant from it. It is observed that some important elements, such as the romantic nationalism, the restoring of the epic genre and the exacerbated sentimentality, are present in the novel and contribute to the maintenance of the imaginary that still exists around the Farroupilha Revolution and which was established in the nineteenth century. There is also the influence of other aesthetics, of different eras and styles, which are entangled in the novel and provide the reader with the safety of what is already known.